Are Early Warning Scores documented accurately and correctly by nurses: A Critical Review - Bhogal, Gurpreet Kaur (2013)
Aim: The aim of this dissertation is to critically review the literature surrounding the accuracy of nurses’ documentation of the EWS. This critical review aims to examine the quality and methods of the current research on EWS documentation and whether these can be enhanced in any way.